SIKAP MASYARAKAT SEHUBUNGAN DENGAN HILANGNYA MINYAK GORENG DARI PASAR DI JAKARTA - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2021)
Background: The loss of cooking oil in the market caused by the supply of oil from distributors is not much, this is because there is no intentional element from the oil producer but the oil producing industry has purchased raw materials at international standard prices so industry players also cannot process it because the government is the one who lowering prices does not look at the regulation of the supply of fresh palm fruit, which if produced according to government policies, industry players will be disadvantaged in other words prices are unstable according to world standards. Purpose: to find out the attitude of the community regarding the loss of cooking oil in the market and what sellers and buyers do. Method: problem solving with a qualitative descriptive approach by conducting community service research. Result: Consumers who do not get cheap cooking oil respond by buying packaged oil at traditional markets and stalls closest to consumers' homes, besides that there are also consumers who work with sellers to deposit money in advance so that if the goods come, they are set aside for immediate use. Consumers who have ordered, here are also consumers who don't have much money to stock up on cooking oil, they borrow money from mobile banks with a double return of the loan, but this is considered effective and very urgent.